ANALISIS KETERAMPILAN GEOMETRI SISWA KELAS X DALAM MENYELESAIKAN SOAL SEGIEMPAT BERDASARKAN LEVEL VAN HIELE - Afifah, Arum Hikmahtul; Susanto, Susanto; Sugiarti, Titik; Sunardi, Sunardi; Monalisa, Lioni Anka (Department of Mathematics Education , University of Jember, 2019)
This study aims to determine the geometry skills of class X students in solving quadrilateral questions based on van Hiele's level. The research subjects were 6 students of grade X MIPA 4 in SMA Negeri 1 Jember. Students are given van Hiele level classification test questions, geometry skills test questions, and followed by interviews. This type of research is a qualitative descriptive study. The results obtained are students at the rigor level have visual skills, verbal skills, and logic skills. Students at the deduction level have visual and drawing skills. Students at the informal deduction level have visual skills, logic skills, and applied skills. Female students who are at the analysis level have visual skills, verbal skills, logic skills, and applied skills. Male students at the analysis level have visual skills. Students at the visualization level have visual skills.